Dopamine-dependent visual attention preference to social stimuli in nonhuman primates - Yamaguchi, Yoshie (Psychopharmacology (Berl), 2017)
RATIONALE: Dopamine (DA) plays a central role in reward processing. Accumulating evidence suggests that social interaction and social stimuli have rewarding properties that activate the DA reward circuits. However, few studies have attempted to investigate how DA is involved in the processing of social stimuli. OBJECTIVES: In this study, we investigated the effects of pharmacological manipulations of DA D1 and D2 receptors on social vs. nonsocial visual attention preference in macaques. METHODS: Japanese macaques were subjected to behavioral tests in which visual attention toward social (monkey faces with and without affective expressions) and nonsocial stimuli was examined, with D1 and D2 antagonist administration. RESULTS: The macaques exhibited significantly longer durations of gazing toward the images with social cues than did those with nonsocial cues. Both D1 and D2 antagonist administration decreased duration of gazing toward the social images with and without affective valences. In addition, although D1 antagonist administration increased the duration of gazing toward the nonsocial images, D2 antagonism had no effect. CONCLUSIONS: These results suggest that both D1 and D2 receptors may have roles in the processing of social signals but through separate mechanisms.